Endovascular Repair of Aortobronchial Fistula due to Saccular Aneurysm of Thoracic Aorta - Konstantinos Tigkiropoulos; Kyriakos Stavridis; Ioannis Lazaridis; Nikolaos Saratzis (Case Reports in Vascular Medicine)
Aortobronchial fistula (ABF) is a rare condition which can be lethal if left untreated. Open surgical treatment carries high morbidity and mortality. Recent advances in endovascular technology have made thoracic endovascular aortic repair (TEVAR) the treatment of choice. We present a successful endovascular repair of aortobronchial fistula due to a saccular aneurysm of descending thoracic aorta.